Original articleNeuroprotective effect of rotigotine against complex I inhibitors, MPP+ and rotenone, in primary mesencephalic cell culture - Radad, Khaled; Scheller, Dieter; Rausch, Wolf-Dieter; Reichmann, Heinz; Gille, Gabrielle (Folia Neuropathologica, 2014)
Introduction: Dopamine agonists are suggested to be more efficacious in treating Parkinson’s disease (PD) as they have neuroprotective properties in addition to their receptor-related actions. Aim of the study : The present study was designed to investigate the neuroprotective effects of rotigotine, a D3/D2/D1 dopamine receptor agonist, against the two powerful complex I inhibitors, 1-methyl-4-phenylpyridinium (MPP + ) and rotenone, in primary mesencephalic cell culture relevant to PD. Material and methods : Primary mesencephalic cell cultures were prepared from embryonic mouse mesencephala at gestation day 14. Three sets of cultures were treated with rotigotine alone, rotigotine and MPP + , and rotigotine and rotenone to investigate the effect of rotigotine on the survival of dopaminergic neurons against age-, MPP + - and rotenone-induced cell death. At the end of each treatment, cultures were fixed and stained immunohistochemically against tyrosine hydroxylase (TH). The effect of rotigotine against rotenone-induced reactive oxygen species (ROS) production was measured using CH-H2DCFDA fluorescence dye. Results: Rotigotine alone did not influence the survival of tyrosine hydroxylase immunoreactive (THir) neurons except at 10 µM, it significantly decreased the number of THir neurons by 40% compared to untreated controls. Treatment of cultures with 0.01 µM rotigotine rescued 10% of THir neurons against MPP + -induced cell death. Rotigotine was also found to significantly rescue 20% of THir neurons at 0.01 µM of rotenone-treated cultures. Using of CH-H2DCFDA fluorescence dye, it was found that rotigotine significantly attenuated ROS production compared to rotenone-treated cultures. Conclusions : Rotigotine provides minor protection against MPP + and rescues a significant number of THir neurons against rotenone in primary mesencephalic cell cultures relevant to PD.